Dimethyl sulfoxide (DMSO) degradation by electro-fenton process - Colades, James I. (2013)
Treatment of dimethyl sulfoxide (DMSO), a recalcitrant pollutant of the semiconductor industry, remains a challenge to the industry since conventional wastewater treatment is incapable of complete treatment of DMSO which results to the production of toxic and noxious intermediated. The problem requires the application of advanced oxidation process (AOPs) which produces hydroxyl radicals, a powerful and non-selective oxidant. Electro-Fenton, an AOP, was used in this study to degrade DMSO using a double-cathode electrochemical reactor. Optimization of operating variables by Box-Behnken Design of Experiment showed that optimum conditions are 1.95, 2.11 mM and 26 mM for pH, Fe²⁺ loading, and H₂O₂ loading, respectively, which resulted to 100% DMSO removal, close to the value of 99% DMSO removal predicted by the model. A new proposed kinetic model provided better fit to experimental data than the conventional 1st and 2nd order reaction kinetics. Photoelctro-Fenton performed best among the processes studied; however, it consumed 9 times energy compared to electro-Fenton process. Dissolved inorganic ions reduced degradation efficiency in increasing intensity as follows: chloride, fluoride, and phosphate. The electro-Fenton process was also applied to a real TFT-LCD wastewater with 68% TOC and 79% COD removal. This study shows the feasibility of the application of electro-Fenton treatment on and its results will aid in the design of large-0scale electro-Fenton reactors for treatment of DMSO-containing industrial wastewater.